Platelet HPA-1 a/HPA-1 b polymorphism and the risk of periprocedural myocardial infarction in patients undergoing elective PCI. (August 2014) - Verdoia, Monica; Secco, Gioel Gabrio; Barbieri, Lucia; Cassetti, Ettore; Schaffer, Alon; Sinigaglia, Fabiola; Marino, Paolo; Suryapranata, Harry; De Luca, Giuseppe; on behalf of the Novara Atherosreclerosis Study Group (NAS)
Abstract Periprocedural myocardial infarction (PMI) represents a relatively common complication of percutaneous coronary intervention (PCI) and large interests have been focused on platelets in order to prevent such a complication. The single nucleotide polymorphism Leu33Pro of platelet glycoprotein IIIa has been related to an increased platelet reactivity, a lower response to antiplatelet agents and higher risk of stent restenosis. Therefore, aim of our study was to evaluate the impact of this polymorphism on PMI in elective patients undergoing PCI. Our population is represented by 422 consecutive patients with cardiac biomarkers within normality undergoing elective PCI. We measured cardiac biomarkers (CK–MB and Troponin I) at baseline, and 8, 24 and 48 hours after the procedure. For all subjects, we performed genetic analysis to assess the presence of Leu33Pro polymorphism. A total of 136 patients (32.2%) were polymorphic. Those patients were younger (p = 0.03) and more often dislypidemic (p = 0.01). Angiographic features did not differ according to genetic status. Pharmacological treatment pre and during angioplasty was similar. PCI-related complications did not differ according to genotype, with the only exception of higher rate of distal embolization in polymorphic patients. However, Leu33Pro polymorphism was not associated with increased risk of periprocedural myonecrosis and PMI even after correction for baseline differences, (respectively OR = 1.22 [0.81–1.84], p = 0.34 for myonecrosis and OR = 1.66 [0.85–3.23]; p = 0.14 for PMI). At subgroup analysis, the Leu33Pro substitution was associated with higher risk of PMI only among diabetics (adjusted OR = 4.46 [1.12–17.76], p = 0.03). Among patients undergoing elective PCI, the polymorphism Leu33Pro of platelet glycoprotein IIIa is associated with increased risk of PMI only in diabetic patients.